Facile synthesis of layered Co(OH)2 deposited g-C3N4 for activating peroxymonosulfate to degrade organic pollutants. (31st August 2021) - Zhang, Yingxue; Qu, Jianyu; Ding, Fangjun; Kong, Yujiao; Su, Xiurong; Xu, Xingliang
Abstract : Layered Co(OH)2 deposited g-C3 N4 is found to be highly active in the activation of peroxymonosulfate (PMS) for pollutant removal. Abstract : Sulfate radical-based advanced oxidation technologies (SR-AOTs) are very effective solutions to remove organic pollutants from wastewater. Nevertheless, difficulties remain in finding an efficient and environmentally friendly catalytic system to activate peroxymonosulfate (PMS) for the oxidation process. In this work, a simple impregnation method for synthesizing layered Co(OH)2 deposited g-C3 N4 (Co(OH)2 /g-C3 N4 ) was developed. The as-obtained Co(OH)2 /g-C3 N4 showed excellent performance in the destruction of various organic pollutants through PMS activation. The structure, morphology and composition of Co(OH)2 /g-C3 N4 were analyzed using diverse characterization methods. Various experimental parameters such as catalyst loading, initial PMS concentration, pH, reaction temperature and initial organic pollutant concentration were studied in detail. The obtained Co(OH)2 /g-C3 N4 composite can completely degrade Rhodamine B (RhB) with a high reaction rate constant of 0.460 min −1 under the optimal conditions, which was much higher than those of Co(OH)2, g-C3 N4 and many other metal catalysts. This was because the synergistic effect between the layered Co(OH)2 with sufficient active sites and electron-rich g-C3 N4 with good electron transfer ability can accelerate the activation of PMS. Besides, radical quenching experiments indicated that sulfate radicals (SO4 ˙ − ) were the major active radicals in the PMS activation process. Finally, the degradation pathways and a reasonable reaction mechanism of the Co(OH)2 /g-C3 N4 /PMS system for RhB removal were put forward. The study revealed that Co(OH)2 /g-C3 N4 could provide appropriate strategies for the removal of organic pollutants in aqueous environments.